Modelling demographic impacts of a growing Arctic fishery on a seabird population in Canada and Greenland. (November 2018) - Anderson, Christine M.; Iverson, Samuel A.; Black, Amie; Mallory, Mark L.; Hedd, April; Merkel, Flemming; Provencher, Jennifer F.
Abstract: In Baffin Bay and Davis Strait, reports indicate that Northern Fulmars (Fulmarus glacialis ) are vulnerable to bycatch in the fisheries for Greenland Halibut ( Reinhardtius hippoglossoides ). We modeled the potential current and future impacts the expanding halibut fishery may have on fulmar populations in the region using population viability analysis. By varying age-specific bycatch vulnerability, detectability, and the size of the at-risk population, we tested how different scenarios may influence population trajectories. From 2011 to 2015, the bycatch rate of fulmars was approximately 212 (SD ± 111) individuals per year. This could cause declines (−12%) over three generations (66 years) at the three colonies closest to the fishing grounds. However, declines could be as high as −33% over this same period if unobservable bycatch is considered, and as low as −0.4% if bycatch is distributed among a larger population. Several uncertainties we modeled could be reduced by improving how bycatch data are recorded by at-sea observer programs. Highlights: Approx. 212 Northern Fulmars/year are bycaught in the Baffin Bay-Davis Strait Halibut Fishery. Demographic effects could range from −0.4% to −33% declines over 3 generations. Colony location of bycaught birds is one of the biggest sources of uncertainty. Demographic impacts likely to increase as sea ice decreases and this fishery grows.